Model-based heuristic for counter assignment problem with operational constrains: A case study - Ornek, M. Arslan; Ozturk, Cemalettin; Sugut, Ipek (Journal of air transport management, 2019)
Check-in counters have a great impact on the quality of service for airports. It is airport management's responsibility to provide check-in counters to airlines. Each check-in group (i.e., flights sharing the same resources) has a counter demand and this gives rise to a counter assignment problem. This is due to a number of objectives and constraints under which check-in groups are allocated to check-in counters. In this paper, we develop an Integer Programming model to optimally assign incoming flights to check-in counters and propose a decomposition algorithm to solve the allocation problem in a reasonable time. Computational results from a medium sized airport indicate a better utilisation of check-in counters, enabling airport management to reduce/postpone investment in additional check-in counters. •Counter assignment problem originated from a real case is studied.•An integer programming model is developed.•A model based heuristic is developed.•Data is made available for researchers.